THE ROLE OF EDUCATION IN THE INFORMATION SOCIETY - WARZOCHA, Tomasz (Trends in education, 2012)
The article was presents issues related to education in the information society, educational objectives, characteristics, which should stand out adequate education for the knowledge society, which functions full teacher in the information society.
Keywords: education; new technologies; the educational process; information society; teacher workshop.